Optimal Sensors Placement for Flood Forecasting Modelling. (2015) - Fattoruso, Grazia; Agresta, Annalisa; Guarnieri, Guido; Lanza, Bruno; Buonanno, Antonio; Molinara, Mario; Marrocco, Claudio; De Vito, Saverio; Tortorella, Francesco; Francia, Girolamo Di
Abstract: Numerical models are instrumental to more effective flood forecasting and managementservices though they suffer from numerous uncertaintysources. An effective model calibration is hence essential. In this research work, a methodology of optimal sampling design has been investigated and developed forwater drainage networks. Optimal hydrometer sensors locationsalong the Amato River (South Italy)have been defined by optimizing a two-objective function that maximizes the calibrated model accuracy and minimizesthe total metering cost. This problem has been solved by using an enumerative search solution, run on the ENEA/CRESCO HPC infrastructure, evaluating the exact Pareto-front byefficient computational time.